2016
DOI: 10.5005/jp-journals-10013-1259
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations in Osteomeatal Complex among Patients undergoing Functional Endoscopic Sinus Surgery

Abstract: Aims: To study the anatomical variations of osteomeatal complex and the importance of preoperative computed tomography (CT) in patients with chronic sinusitis undergoing functional endoscopic sinus surgery. We studied the different variations and their frequency of occurrence. Materials and methods: A total of 100 patients undergoing endoscopic sinus surgery were studied by nasal endoscopy, CT scanning, and at the time of definitive surgery, variations were recorded. Results: The frequency of occurrence of sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…The study by showed the incidence of HC 3.5% which is close to our result [10]. The incidence of Onodi cells in our study is 2.7% which is lowest incidence in comparison with other studies which showed the incidence of OC ranges from 8-13% [11]. These cells also known as sphenoethmoidal cells, they are the most posterior ethmoid air cells that extend laterally and located anterosuperior to sphenoid sinus [5].…”
Section: Anatomical Variation Of Frontal Sinussupporting
confidence: 86%
See 1 more Smart Citation
“…The study by showed the incidence of HC 3.5% which is close to our result [10]. The incidence of Onodi cells in our study is 2.7% which is lowest incidence in comparison with other studies which showed the incidence of OC ranges from 8-13% [11]. These cells also known as sphenoethmoidal cells, they are the most posterior ethmoid air cells that extend laterally and located anterosuperior to sphenoid sinus [5].…”
Section: Anatomical Variation Of Frontal Sinussupporting
confidence: 86%
“…Among The anatomical variants the most frequent variant was deviated nasal septum which can be bony, cartilaginous, or combination. The divergence of septum from the midline causes lateral displacement of middle conch leading to nasal obstruction [11]. Our study also shows 14.3% of patients with nasal septum spur, which is bony deformity that may obstruct the nasal air flow, and may be associated nasal septal deviation.…”
Section: Nasal Septum Variantssupporting
confidence: 52%
“…Recently, diagnostic nasal endoscopic evaluation of the nose and paranasal sinuses is a routine component for evaluating patients with evidence of suspected chronic sinusitis and the patients with significant findings are evaluated with Computed Tomography (CT) of the paranasal sinuses. 9 Diagnostic Nasal Endoscopy (DNE) and computerised tomography plays a role in diagnosis and to identify the variations in paranasal sinuses. Precise descriptions of anatomical variations are very important in achieving perfect diagnosis and successful endoscopic sinus surgeries.…”
Section: Resultsmentioning
confidence: 99%
“…But, they predispose the individual to chronic sinusitis. 9 The patients underwent functional endoscopy sinus surgery by Messerklinger technique for the treatment of chronic sinusitis. Patients with unilateral sinusitis underwent surgery only on the diseased side.…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to various literatures in the past. Narendra kumar and Subramaniam 9 who Presented it as 76% whereas Turnaet al 10 The strengths of the study are along with a study of incidence of various individual anatomical variants, detailed knowledge was gained about concomitant existence of two or more variations in the same patient. Limitations being, since it included only those people who presented to the ENT OPD with complaints regarding nose and paranasal sinuses, there might be a bias in extending the results to the general population.…”
Section: Discussionmentioning
confidence: 99%